Indah Sebati Sdn Bhd / Nur Nabila Shafiqah Sulaiman - Sulaiman, Nur Nabila Shafiqah (UiTM Cawangan Johor Kampus Pasir Gudang, 2014)
The training is practical training method that are important to each student to each students as they can strengthen their knowledge and work experience to a student. To exposed student to the working environment in real that allow students to look for opportunities to gains work experience in face in a real working environment. Ensure that every students learns the knowledge and experience new possibilities in class but construed in accordance with the course taken. It is also a requirement for students to pass their for student to pass their diploma in Civil Engineering in UiTM.